Physico-Chemical, Mineral, Amino Acid Composition, in Vitro Antioxidant Activity and Sorption Isotherm of Pithecellobium dulce L. Seed Protein Flour - Rao, Galla Narsing (Journal of Food and Pharmaceutical Sciences, 2013)
Pithecellobium dulce L. seed protein flour (PSPF) was evaluated for the chemical, mineral, amino acid composition, in vitro antioxidant activity and sorption isotherm. Protein content was found to be 39.22% PSPF. Calcium (48 mg) and phosphorus (542 mg/100 g) were observed in major quantities. Major amino acids were determined as glutamic acid, arginine, aspartic acid, lysine, valine, threonine and leucine. The ratio of essential to nonessential amino acids was observed to be 0.61. Essential amino acids were higher than the reported amounts for 70 kg person (100 g seed protein flour) as per FAO/WHO/UNU requirements. DPPH, Inhibition (25-73%) and ferric reducing power OD (0.136-0.523) are increased with increasing concentration of PSPF from 3-15 mg. SDS-PAGE of PSM and PSPF showed similar polypeptides with molecular weights from 205 kDa to 12 kDa. The IMC (10.34%) of PSPF, which equilibrated at 69% RH, indicated the non-hygroscopic nature.